Evaluation of Blackboard Learning Management System for Full Online Courses in Western Branch Colleges of Qassim University - Alturise, Fahad (International Journal of Emerging Technologies in Learning (iJET), 2020)
With the advance in information technology, higher education institutes begun to transit from existing traditional teaching method alternate blackboard Learning Management System (LMS). In this context, western branch Colleges of Qassim University in the Kingdom of Saudi Arabia for the first-time started blackboard learning management system for e-learning in the academic year of 2016. At first stage of project, Deanship of E-Learning launched the e-courses for Islamic 101 and Islamic 102 at full online in the university and trained all faculties and students to the new e-course full level program. Based on the new developed full online courses, a survey was conducted in college of western branch in Qassim University regarding difficulties, limitations, faculty members and student’s satisfaction regarding blackboard LMS using full online course on campus. Detailed evaluation of survey concludes that devel-oped e-courses is a new step but required significant work for improvements.